Jean-Philippe Toussaint en Italie : les effets du champ littéraire sur sa réception symbolique - Chiara Elefante (MediAzioni)
The aim of this study is to analyse the symbolic reception of Jean-Philippe Toussaint's work translated into Italian from the perspective of the sociology of translation. In the first part of the article, I will present Toussaint’s translations published in Italy. In the second part, I will put their history in relation to the evolution of Italian publishing in the decades 1980-2020, and in the third part, I will analyse Toussaint's symbolic reception in Italy in order to understand the effects of the Italian publishing field on his reception, as well as the role of the various intermediaries who have contributed to the critical debate in the Italian context.